Relationship between Types of Cervical SpineTrauma and Occurrence of Neurological Deficits - Syaiful Anwar; Agus Hadian Rahim; Farhan Anwary (Faculty of Medicine Universitas Padjadjaran, 2017)
Background: About 3,500 people died each year due to neck injury, according to a study in the USA. Trauma at cervical spine level causes injury in soft tissue, cervical vertebrae, and spinal cord that can cause neurological deficits. The aim of this study was to analyze the relationship between type of cervical trauma and the occurrence of neurological deficits.Methods: An analytic study was carried out to 121 medical records of patients diagnosed with cervical spine trauma at Dr. Hasan Sadikin General Hospital Bandung in the period of January 2010−December 2012. Data were classified according to age, sex, period of initial visit to hospital, mechanism of trauma, cervical trauma type, fracture’s or dislocation’s location (without any other vertebral injury) and neurological status. The collected data were analyzed using Chi-Square test and presented in tables.Results: There were 121 cases of cervical spine trauma. Most patients were male and in the productive age group (30−44 years). Most of the initial visits to the hospital were in 2010 and most of the mechanism was traffic accident (46.28%), while soft tissue injury was the most common type of cervical trauma (54.54%) and lower cervical vertebrae was the most common location of fractures or dislocations (76.36%). Sixty two patients were recorded with neurological deficits. Chi-Square test of relationship between the type of cervical trauma and the occurrence of neurological deficit was statistically significant (p=0.000).Conclusions: There is relationship between the type of cervical trauma and occurrence of neurological deficits. DOI: 10.15850/amj.v4n2.1084